Abdominal hypertension characterised by severe haemodynamic changes as a complication of percutanous nephrolithotomy - Ozer, Ayse Belin; Firdolas, Fatih; Aydin, Ahmet; Erhan, Omer L. (BMJ Publishing Group, 2012)
Percutanous nephrolithotomy (PCNL) was performed on a patient in a prone position. During the first hour of intervention, some unwanted haemodynamic complications arose, which included a decrease in systemic blood pressure, an increase in heart rate and an increase in peak inspiratory pressures. Owing to worsening of those unexplained haemodynamic abnormalities, surgery was terminated. As the patient turned from prone to supine position, abdominal distention was noticed. Later, 3 litres of fluid were removed from the abdomen via peritoneal lavage. Upon fluid removal, a dramatic haemodynamic improvement was observed. The problem was thought to have been caused by a technical error in placing the dilator inside the abdomen, which allowed the irrigation fluid to accumulate inside the abdominal cavity. The aim of this presentation is to raise awareness of intra-abdominal hypertension when the aforementioned haemodynamic abnormalities are detected during PCNL. Early detection and treatment may prevent morbidity and mortality in similar cases. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: atropine; fentanyl; neostigmine; propofol; vecuronium; abdominal compartment syndrome; abdominal distension; adult; anesthesia induction; article; artificial ventilation; blood cell count; blood oxygen tension; blood pressure monitoring; breathing rate; case report; disease classification; hemodynamic parameters; hemoglobin determination; human; hypotension; intraabdominal hypertension; kidney blood flow; male; patient monitoring; patient positioning; percutaneous nephrolithotomy; peritoneum lavage; preoperative evaluation; priority journal; surgical technique; tachycardia; tidal volume